PENGARUH MOTIVASI KERJA, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT (Studi Empiris Pada RS PKU Muhammdiyah Gombong) - Sri Ramlah; Tyan Fathurrokhman; Wilson Chandra Teguh Pratama (MANAJEMEN DEWANTARA, 2025)
This research aims to examine and analyze the influence of work motivation, workload, and work environment on nurse performance (An Empirical Study at PKU Muhammadiyah Hospital Gombong). The research method used is quantitative, with the research sample consisting of nurses working at RS PKU Muhammadiyah Gombong, totaling 50 nurses. The research sample was taken using the proportional random sampling method. The data analysis technique used is Multiple Linear Regression with SPSS25 software. The benefits of this research are two fold: from the theoretical perspective, it contributes to the field of human resource management, particularly in the development of concepts related to work motivation, workload, and work environment. Whereas the Practical Benefits Practically, this research serves as a consideration for the leadership of RS PKU Muhammadiyah Gombong in order to enhance the development of Human Resource Management knowledge at RS PKU Muhammadiyah Gombong, particularly regarding motivation, workload, and work environment. The results obtained in this study indicate that work motivation has a positive influence, while workload and work environment have a negative impact on the performance of nurses at RS PKU Muhammadiyah Gombong. Work motivation has a positive impact on the improvement of nurse performance at RS PKU Muhammadiyah Gombong. Workload has a negative impact on the performance of nurses at RS PKU Muhammadiyah Gombong, and the work environment also negatively affects the performance of nurses at RS PKU Muhammadiyah Gombong. Keywords: Motivation, Workload, and Work Environment, Nurse Performance.